Results of an observational study of the safety of antimicrobial scratching in 15 children with cystic fibrosis at the inpatient stage of treatment at the State Budgetary Healthcare Institution “Morozovskaya Children’s City Clinical Hospital of Moscow Healthcare Department” from 12.12.2019 to 30.03.2020 - A. V. Vlasova; T. A. Tenovskaya (Здоровье мегаполиса)
The aim of this pilot non-interventional observational research was to assess the prevalence of adverse events associated with the use of antimicrobial drugs in children with cystic fibrosis, including the situations with the absence of the expected therapeutic effect in terms of clinical manifestations at the stage of hospital treatment. The observation group included 15 patients with cystic fibrosis hospitalized at the Morozovskaya Children’s City Clinical Hospital of Moscow Healthcare Department from 12.12.2019 to 30.03.2020. In the article there was carried out the analysis of the safety of antimicrobial drugs use by all children hospitalized with cystic fibrosis. During the study period, there were no serious adverse events caused by the use of all drugs. Adverse events were reported in 3 out of 15 patients included in the observational study with the use of 4 drugs. Thus, in our study the frequency of adverse events connected with the use of antimicrobial drugs by the patients with cystic fibrosis is 11.8%, which does not exceed the rates for the general population of patients receiving antimicrobial drugs registered for medical use in the United States and the European Union (according to experts 14-20 %). During the observation period in hospital of patients with cystic fibrosis, there was no established fact of pharmacotherapy ineffectiveness. This pilot non-interventional observational study has serious limitations for analysis, therefore, in accordance with letter of the Federal Service for Surveillance in Healthcare (04/01/2020 № 02-17376/20), based on the results of a meeting at the Federal State Budgetary Scientific Institution “Moscow State Scientific Center named after Academician N.P. Bochkov» federal medical institutions providing medical care to children with cystic fibrosis continue to implement the program for monitoring the effectiveness and safety of antibacterial drugs used in patients with cystic fibrosis during hospitalization on permanent basis.